2020
DOI: 10.1021/acs.jmedchem.0c01195
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in β2-Agonists for Treatment of Chronic Respiratory Diseases and Heart Failure

Abstract: β 2 -Adrenoceptor (β 2 -AR) agonists are widely used as bronchodilators. The emerge of ultralong acting β 2 -agonists is an important breakthrough in pulmonary medicine. In this review, we will provide mechanistic insights into the application of β 2agonists in asthma, chronic obstructive pulmonary disease (COPD), and heart failure (HF). Recent studies in β-AR signal transduction have revealed opposing functions of the β 1 -AR and the β 2 -AR on cardiomyocyte survival. Thus, β 2 -agonists and βblockers in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 281 publications
0
4
0
1
Order By: Relevance
“…Our strategy for the synthesis of β 2 AR 8P,Ub 7 is depicted in Figure 2a. β 2 AR 8P,Ub 7 was divided into four segments: β 2 AR 1−350 (2), β 2 AR 351−377,Aux,4P -NHNH 2 (8), Ub 1−75 -NHNH 2 (9), and β 2 AR 378−413,4P (5). NCL was chosen for the assembly of 8, 9, and 5 to give the C-terminal modified β 2 AR 351−413,8P,Ub -NHNH 2 (10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our strategy for the synthesis of β 2 AR 8P,Ub 7 is depicted in Figure 2a. β 2 AR 8P,Ub 7 was divided into four segments: β 2 AR 1−350 (2), β 2 AR 351−377,Aux,4P -NHNH 2 (8), Ub 1−75 -NHNH 2 (9), and β 2 AR 378−413,4P (5). NCL was chosen for the assembly of 8, 9, and 5 to give the C-terminal modified β 2 AR 351−413,8P,Ub -NHNH 2 (10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…G-protein-coupled receptors (GPCRs) are the largest class of signaling receptors in the human genome and are targeted by over 30% of modern pharmaceuticals. One archetype GPCR is the β 2 adrenergic receptor (β 2 AR), which is targeted by respiratory and asthma drugs and has been extensively studied. β 2 AR is a key mediator of cellular signaling in response to extracellular stimuli such as the hormones epinephrine and norepinephrine and can be coupled with downstream transducers, including Gs and Gi protein subtypes, GPCR kinases, and β-arrestins, to mediate a wide variety of physiological functions ranging from the control of vascular tone and cardiac performance to metabolism. Recent studies revealed that post-translational modifications (e.g., phosphorylation and ubiquitination) at the C-terminal tail can play essential roles in recruiting β-arrestin for β-arrestin dependent signaling and receptor internalization and regulating endocytic trafficking and degradation. , However, the exact mechanism of how β 2 AR post-translational modifications including phosphorylation and ubiquitination regulate receptor functions at the molecular level has yet to be fully elucidated, primarily because access to homogeneous samples of β 2 AR bearing a well-defined modified pattern is very difficult using either direct cellular expression or in vitro enzymatic methods …”
Section: Introductionmentioning
confidence: 99%
“…Ранее в исследованиях показано, что постоянный прием препаратов для контроля БА увеличивает риск сердечно-сосудистых заболеваний [15,23]. Этот факт имеет большое клиническое значение при принятии решения о выборе базисной терапии больным БА, в особенности у больных старшего возраста.…”
Section: Discussionunclassified
“…The β 1 -AR couples to G s protein while the β 2 -AR and the β 3 -AR couple to both G s and G i proteins [22]. The β 2 -AR can 'switch' its G protein-coupling preference from G s to G i and this is dependent on the phosphorylation of the β 2 -AR by PKA [23].…”
Section: Differential Effects Of Cardiac β-Ar Subtype Signaling In Re...mentioning
confidence: 99%
“…Agonist-induced receptor internalization is more rapid and obvious in β 2 -ARs, but less sensitive in β 1 -ARs [50]. Overall, homologous desensitization reduces G protein-mediated signal transduction, and is believed to produce a beneficial effect on the failing heart by restricting the β 1 -ARmediated cardiotoxic pathway [22], but it may also, to a lesser extent, contribute to the functional decline of the failing heart by causing β 2 -AR subsensitivity [39].…”
Section: Desensitizationmentioning
confidence: 99%